High-Dose-Rate (192)Ir Brachytherapy Dose Verification: A Phantom Study - Nikoofar, Alireza (Iran J Cancer Prev, 2015)
BACKGROUND: The high-dose-rate (HDR) brachytherapy might be an effective tool for palliation of dysphagia. Because of some concerns about adverse effects due to absorbed radiation dose, it is important to estimate absorbed dose in risky organs during this treatment. OBJECTIVES: This study aimed to measure the absorbed dose in the parotid, thyroid, and submandibular gland, eye, trachea, spinal cord, and manubrium of sternum in brachytherapy in an anthropomorphic phantom. MATERIALS AND METHODS: To measure radiation dose, eye, parotid, thyroid, and submandibular gland, spine, and sternum, an anthropomorphic phantom was considered with applicators to set thermoluminescence dosimeters (TLDs). A specific target volume of about 23 cm(3) in the upper thoracic esophagus was considered as target, and phantom planned computed tomography (CT) for HDR brachytherapy, then with a micro-Selectron HDR ((192)Ir) remote after-loading unit. RESULTS: Absorbed doses were measured with calibrated TLDs and were expressed in centi-Gray (cGy). In regions far from target (≥ 16 cm) such as submandibular, parotid and thyroid glands, mean measured dose ranged from 1.65 to 5.5 cGy. In closer regions (≤ 16 cm), the absorbed dose might be as high as 113 cGy. CONCLUSIONS: Our study showed similar depth and surface doses; in closer regions, the surface and depth doses differed significantly due to the role of primary radiation that had imposed a high-dose gradient and difference between the plan and measurement, which was more severe because of simplifications in tissue inhomogeneity, considered in TPS relative to phantom.